(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to know the effect of systemic thinking strategy and testing the according to the strategy by applying it to a sample of students from the Department of the theater Arts / Institute of Fine Arts / third stage To achieve the goals of the research، the researcher developed following hypotheses: Null hypothesis (1): There is no statistically significant difference at the level of significance (0.05) between the average scores of students of the experimental group that were studied according to systematic thinking skills and the mean of the scores of the control group that were studied according to the usual method about their answers to the paragraphs of the cognitive achievement test for the course of methods of teaching art education (before). Null hypothesis (2): There is no statistically significant difference at the level of significance (0.05) between the average scores of students of the experimental group that were studied according to systematic thinking skills and the mean of the scores of the control group that were studied according to the usual method about their answers to the paragraphs of the cognitive achievement test for the course of methods of teaching art education (After). It turned out that there were statistically significant differences between the experimental group and the control in the cognitive achievement test and in favor of the experimental group، as the minimum value of (Man Weteny) reached zero (which is smaller than the value of Man Weteny table). The amount (64) is at the level of significance (0.05)، which indicates that the experimental group is better with the post-cognitive achievement test، as the average of the calculated experimental grades (23) is greater than the value of the average ranks in the control group of (8) and this confirms the preference of the group Pilot in the test (remote). One of the research conclusions is the effectiveness of the systemic thinking strategy used in teaching the subject of teaching methods of art education، as it is based on the student’s practice of mental processes from analysis، composition and conclusion. - Education according to the systemic thinking strategy has an effect in providing a positive role for students through the researcher’s observation of their participation in activities and training، and raised the questions for discussion. In light of the findings of the research، the researcher recommends the following: - Using systemic thinking strategy in teaching، especially teaching art education in fine arts institutes. Training of technical education teachers and teachers on how to use the systemic thinking strategy and applying the foundations and steps of this strategy in the courses held by the Ministry of Education. Complementing the current research، the researcher suggests conducting the following studies: - Conducting a comparative study between systemic thinking strategy and other educational models، among others، to demonstrate the most effective achievement. - Conducting a study on using the systemic thinking strategy in other subjects.